Analisis Kebijakan dalam Mengatasi Problematika Pendidikan untuk Meningkatkan Kualitas Pendidikan di Indonesia - Nur Dahyanti; Sylvi Marsella Diastami; Azra Humaira; Tengku Darmansah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Education is one of the main pillars in human resource development in Indonesia, however the quality of education still faces various challenges, such as unequal access and low quality of teaching. This research aims to analyze the education policies that have been implemented by the government in an effort to improve the quality of education in Indonesia. Through a qualitative approach, policy analysis is carried out to identify factors that influence policy effectiveness and its impact on society. The results of the analysis show that although there are programs such as compulsory education and increasing teacher competency, the gap between the policies formulated and their implementation is still a major problem. Therefore, a more inclusive and participatory approach is needed in formulating education policies to ensure that every policy taken is able to answer local needs and improve the overall quality of education.